Kritik Atas Penafsiran Ayat-Ayat Khilafah - Lufaefi Lufaefi (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2018)
The Qur'an is a revelation that explains all matters. Included is the issue of leadership (khilâfah). Regardless of what kind of khilâfah in the Qur'an, there is no doubt that khilâfah is in the spotlight of the divine kalam. Because any matter must be alluded to in the Qur'an. However, what if the interpretation of the verse is diverted to something that does not mean the verse itself? Through the approach of content and context analysis, in al-Wa'ie tafseer found many verses of the Qur'an are interpreted by jumping conclusion, such as QS. al-Baqarah [2]: 30, al-Mâ’idah [5]: 49 and QS. an-Nisâ’ [4]: 59. These verses clearly do not discuss khilâfah, but Rokhmat S. Labib's interpretation comes to the conclusion of obliging to establish the institution of the Islamic State (khilâfah islâmiyyah). Such an interpretation is far from what the verse wants to say, even worthy of politicizing the verses of the Qur'an.